Locust visual response effect induced by the coupling light characteristics of linear detection polarization violet light and different spectrum lights - Liu, Qihang; Yang, Bo; Jiang, Mingyang; Cao, Xinyu; Zhang, Pingchuan; Cui, Jinxin; Zhao, Huiyuan (International Journal of Agricultural and Biological Engineering, 2025)
This study investigated the effects of polarized and spectral light interactions on locust polarotaxic behavior and elucidated the regulatory mechanisms of polarized and spectral lights. Locust visual response effect was investigated using a combined light source system comprising linear detection polarization violet light with various spectrum lights and a response device to explore the interaction mechanism of polarized and spectral lights on locust visual sensitivity characteristics and the specific sensitivity of locust phototaxis and polartaxis. Results indicated that the polarized vector sensitivity of locusts was related to combined light intensity, showing high visual response sensitivity at 0° and 180° under 1000 lx, whereas under rated illumination (150 mW/cm2), the coupled spectrum attributes induced changes in the locusts’ sensitive vectors. UV, violet, and blue lights enhanced the sensitivity at 90° and 270°, and green and orange lights did so at 0° and 180°. Moreover, UV and violet lights enhanced the aggregation and trend sensitivity at 210° and 30°, blue, green and orange lights induced high sensitivity at 0° and 180°. Under increasing illumination, the enhanced effect of light intensity on aggregation sensitivity under blue, green, and orange spectra and on trend sensitivity under orange spectra at 90° and 270° were highly pronounced because of the interaction between heterogeneous spectrum illumination and linear detection polarization vector illumination. Meanwhile, the spectral attribute determined the locust visual response effect, which was affected by the linear detection polarization vector. When illumination increased to rated illumination, coupled light intensity induced a specific vector sensitivity related to optical distance, showing the strongest response sensitivity to 180° under orange spectra and the strongest aggregation and trend sensitivity to 210° under violet spectra due to the interplay of polarization degree, coupling light intensity, and specific vision sensitivity caused by partially polarized light. Then, the locust visual response effect was improved by utilizing the enhancement effect of polarized violet light coupled with violet light at a close range and the inductive effect of polarized violet light coupled with orange light at a long distance, which provide theoretical support for understanding locust polarotactic orientation mechanisms, facilitate the development of polarization induced light sources for attracting locusts.Keywords: Locusta migratoria manilensis, coupling light characteristics, linear detection polarization violet light, different spectrum lights, visual response effectDOI: 10.25165/j.ijabe.20251805.9398Citation: Liu Q H, Yang B, Jiang M Y, Cao X Y, Zhang P C, Cui J X, et al. Locust visual response effect induced by the coupling light characteristics of linear detection polarization violet light and different spectrum lights. Int J Agric & Biol Eng, 2025; 18(5): 39–46.